PENENTUAN NILAI SPF DARI EKTRAK ETANOL DAUN JAMBU AIR (Syzygium aqueum) DAN DAUN KERSEN (Muntingia calabura L.) - Zulkarnain, Iskandar; Aztriana, Aztriana; Hasrawati, A; Jaya, Taufiq; Iksan, Muh.; Mirawati, Mirawati (Fakultas Farmasi UMI, 2024)
Skin is the outer part of the body that is directly exposed to the environment, especially sunlight such as ultraviolet radiation. The skin basically has a defense against the negative effects of UV radiation of sunlight. Excessive sun exposure to the skin can cause skin damage that is acute (fast) and chronic (long). One of the ways used to prevent these negative effects is to use suncreen with a high SPF value. Syzygium aqueum and Muntingia calabura L. are plants that can be utilized as natural sunscreen active ingredients due to the content of polyphenolic compounds and high antioxidant activity values in their leaves. The purpose of this study was to determine the SPF value of ethanol extracts of Syzygium aqueum and Muntingia calabura L. and its protection category. Determination of SPF value was carried out by UV-VIS spectrophotometric method at UV B wavelength (290-320 nm), then the absorbance value obtained was calculated into the Mansur mathematical equation. Determination of sunscreen protection category based on SPF value refers to the provisions of the Food Drug Administrations (FDA). The results showed that the highest SPF value of Syzygium aqueum was obtained at a concentration of 1000 ppm, namely 46.183 with ultra protection category and the highest SPF value of Muntingia calabura L. at a concentration of 1500 ppm, namely 47.975 with ultra protection protection category. Based on these results, Syzygium aqueum and Muntingia calabura L. have the potential to be developed as sunscreen active ingredients with ultra protection category.